2022
DOI: 10.1016/j.molimm.2022.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Humoral response to the BBIBP-CorV vaccine over time in healthcare workers with or without exposure to SARS-CoV-2

Abstract: SARS-CoV-2-specific humoral response was analyzed over time in a group of healthcare workers with or without exposure to SARS-CoV-2, who underwent vaccination with BBIBP-CorV (Sinopharm) vaccine in Argentina. Seroconversion rates in unexposed subjects after the first and second doses were 40% and 100%, respectively, showing a significant increase in antibody concentrations from dose 1 to dose 2 ( p < 0.0001). The highest antibody concentrations were found in younger… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
28
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 10 publications
9
28
1
2
Order By: Relevance
“…However, this humoral response diminished progressively between the 90th to 180th day after the second dose, particularly in the NPI group, where lower anti-S-RBD IgG and NAbs were detected than those PI. The seroconverted proportion in the study was comparable but discretely lower than the results reported on phases 1 and 2 of the BBIBP-Corv-2 clinical trials [ 18 ] and other observational studies [ 19 , 20 , 21 ], although higher than that reported by Lijeskic [ 22 ]. However, we did not find a difference in the proportions of seroconverts according to age group, probably because most of our participants were adults under 50 years, and these differences in the humoral response are primarily observed in older patients.…”
Section: Discussionsupporting
confidence: 42%
“…However, this humoral response diminished progressively between the 90th to 180th day after the second dose, particularly in the NPI group, where lower anti-S-RBD IgG and NAbs were detected than those PI. The seroconverted proportion in the study was comparable but discretely lower than the results reported on phases 1 and 2 of the BBIBP-Corv-2 clinical trials [ 18 ] and other observational studies [ 19 , 20 , 21 ], although higher than that reported by Lijeskic [ 22 ]. However, we did not find a difference in the proportions of seroconverts according to age group, probably because most of our participants were adults under 50 years, and these differences in the humoral response are primarily observed in older patients.…”
Section: Discussionsupporting
confidence: 42%
“…In our study, more female-HCWs took the SARS-CoV-2 vaccine compared to males; however, there was no significant difference in the mean titer levels between males and females as was shown in other studies [ 20 ]. Badano MN et al found higher titer levels in Sinopharm vaccinated female HCWs, but further studies are recommended to evaluate any similar trends in our population [ 21 ].…”
Section: Discussionmentioning
confidence: 93%
“…Similar to our results, Choudhary and his collaborators describe no significant difference in post-vaccination antibody production according to sex and age [ 50 ]. In contrast, another study reported a high level of antibodies in young participants and women [ 53 ]. We also found that the level of IgG seropositivity in subjects vaccinated with Covishield or BBIBP-CorV was not significantly different between the two vaccines (171.7 AU/mL vs. 126.7 AU/mL, respectively) and this is probably due to sample size.…”
Section: Discussionmentioning
confidence: 97%
“…Various studies that were conducted in order to understand the kinetics and durability of antibodies induced after vaccination (ChAdOx1 nCoV-19 and BBIBP-CorV) showed that the immune response persists for up to three to four months, but begins to decline significantly over time [ 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. A study of 122 healthy individuals vaccinated with BNT162b2, where the authors used the same test used in this study to determine the level of antibodies six months after the second dose, reported a decrease in the level of antibodies, but this level was still very high compared to our study (1383 AU/mL).…”
Section: Discussionmentioning
confidence: 99%